The advent of digital government: public bureaucracy and the state in the internet age - Dunleavy, P; Margetts, H (Oxford Internet Institute, 2000)
This paper looks in detail at the impact of e-government change on public administration in the UK, particularly structures and processes associated with New Public Management (NPM) models. The authors describe the key characteristics of NPM change in the UK, and investigate the complexities of the relationship between public administrative regime change and achieving policy goals. They present four possible scenarios for change towards e-government models, focusing particularly on the transformational impact of e-government on existing NPM structures and processes in the UK. The paper draws on examples from abroad such as Australia and the US.